Indicators of ecosystem services in a military Atlantic Forest area, Pernambuco—Brazil. (September 2017) - Guimarães, Helder; Braga, Ricardo; Mascarenhas, André; Ramos, Tomás Barros
Highlights: Ecosystem services indicators were developed for an Atlantic forest military area. Stakeholders were engaged in indicator selection. Particular aspects relevant in those forest-military contexts are discussed. The indicator set can support decision-making/reporting particularly in such areas. Abstract: The use of Ecosystem Services (ES) indicators can help designing, implementing and monitoring public environmental policies. Such indicators may be used as a support tool for natural resources management, like in forest areas, which are important ES providers. In this context, military areas are particularly challenging due to the nature of the activities conducted and the need to conciliate them with ecological protection, without undermining military readiness. It is argued that in addition to technical issues, considering stakeholders' opinions is beneficial for the selection and design of ES indicators. The main aim of this research is to develop forest ES indicators supported by a participatory indicator selection process. A case study is made of an Atlantic Forest area in the Northeast of Brazil, under the jurisdiction of the Brazilian Army. To accomplish that aim, a questionnaire survey was sent to a group of stakeholders in order to evaluate an initial set of proposed 44 indicators for several forest ES. Through a weighting of stakeholders' scores, 25 ES indicators for the Atlantic forest were obtained. The selected indicators portray the study area mainly as a provider of regulating, cultural and habitat services and less of provisioning services, which can be related with military and nature protection restrictions on the use of provisioning ES. Nevertheless, the three top-rated indicators dealt with water availability, regulation and quality (for human consumption). Together with the predominance of water-related ES that was observed (ten out of 25 indicators), this points out the relevance of forest water-related ES in the study area. On the other hand, the specificity of the military context was not clearly reflected by the indicators selected, since most of them are applicable in areas or contexts other than a military one. Alongside indicators expressing the benefits provided by nature, stakeholders' scorings reveal recognition of the importance of biodiversity and resilience of the area. This stresses the importance of biodiversity and resilience to support ES supply, but is also linked with one of the major challenges for managing a military area with high natural value: that of conciliating military activities (that support military readiness) with nature protection. Other forest areas under military or similar particular jurisdiction, often representing a major fraction of national forests, could learn from this approach and identify areas for priority response measures. These indicators could be also a driver to increase and improve environmental management of military training activities and safeguarding natural resources in important ES providing areas like Atlantic forests.